Identification of suitable location for construction of check dam in Manur water shedding area, Tirunelveli District - Gopikumar S; Sundararajan S; Allwyn Kingsly Gladston J; Antony Vasantha Kumar C; Hari Babu K; Jeyakumar K (Global Journal of Ecology - Peertechz Publications, 2021)
In this research article author has focused on the issue of ground water and narrated that in modern civilized society the day today usage of ground water for community utility has been raised. As it is clear that due to change in weather condition the predicted monsoon has been changing its seasonal annual rainfall. Furthermore, the it is suggested that a proper technique should be implemented to preserve the available fresh water, which is need of the hour for dry zone like Manur of Tirunelveli district. A suitable techniques has been suggested for real time implementation which is to be demonstrated in a pilot scale. This research work explores all the possibilities to execute the identification of suitable site selection.